The Politics and Law of 30% Women’s Representation in the Central Kalimantan Provincial DPRD: A Review of the Implications Based on Regulations and Principles of Democratic Justice - Rosa Husadah; Agus Mulyawan; Joanita Jalianery (Dinasti Research, 2025)
Women's participation in governance is a crucial issue in efforts to achieve gender equality and fair democracy. In Indonesia, the 30 percent female quota in legislative bodies is regulated under paragraph (2) of Article 245 of Law No. 7 of 2017 regarding national elections. However, there are still many challenges that must be overcome in the implementation of this policy, especially at the local level. The issues that will be discussed, namely how the challenges in initiatives to enhance woman inclusion in the Central Kalimantan Provincial DPRD, are reviewed from the perspective of applicable regulations and the principles of democratic justice, and how the legal politics regulate the representation of 30% women in the Central Kalimantan Provincial DPRD. This paper uses an empirical legal research method, which is a study based on data obtained from interview observations. Empowerment measures such as political education and training for women need to be strengthened to furnish women with expertise and awareness they need to compete in the political arena. The importance of early political education and public awareness campaigns about gender equality in politics can change existing social perceptions and norms. To bolster women's presence in the Central Kalimantan DPRD, the government, political parties, and the community need to work together to create an environment that supports women's active political participation